The Effect of Educational Intervention on the Improvement of Nontechnical Skills in Circulating Nurses. (15th October 2021) - Kalantari, Reza; Zamanian, Zahra; Hasanshahi, Mehdi; Faghihi, Seyed Aliakbar; Jamali, Jamshid; Niakan, Hadi
Abstract : Background . Nontechnical skills are necessary for clinicians' safe performance and prevention of errors in the operating room. Educational intervention is a useful way to improve these skills, which are a vital area for improvement. Circulating nurses are surgical team members whose work depends heavily on using nontechnical skills. This study is aimed at assessing the effect of an educational intervention on the improvement of circulating nurses' nontechnical skills. Methods . This semiexperimental study was conducted on 300 circulating nurses divided into the intervention and no intervention groups each containing 150 participants. The nontechnical skills were assessed using the circulating practitioners' list of nontechnical skills. Then, the intervention group received training regarding these skills, and the two groups were evaluated again. After all, the data were entered into the SPSS 24 software and were analyzed using descriptive statistics and Wilcoxon and Mann–Whitney tests. Furthermore, Kendall's tau, independent sample t -test, and one-way ANOVA were used for assessment of relationship between median scores and demographics. Results . The results revealed a significant improvement in the scores of all domains of nontechnical skills in the intervention group (p < 0.05 ). The highest and lowest improvements were observed in teamwork (42%) and situational awareness (16.7%), respectively. After the intervention, the scores of some of the behaviors were still below the average level or were not improved significantly. Conclusions . Circulating nurses' nontechnical skills can be improved by educational interventions. However, regarding the low scores or no improvements in the scores of some behaviors, other intervention types such as policymaking and correcting the existing hierarchies in the operating room can be useful to complete the educational interventions.